A patient‐derived explant (PDE) model of hormone‐dependent cancer. Issue 9 (16th August 2018) - Centenera, Margaret M.; Hickey, Theresa E.; Jindal, Shalini; Ryan, Natalie K.; Ravindranathan, Preethi; Mohammed, Hisham; Robinson, Jessica L.; Schiewer, Matthew J.; Ma, Shihong; Kapur, Payal; Sutherland, Peter D.; Hoffmann, Clive E.; et al.
Abstract : Breast and prostate cancer research to date has largely been predicated on the use of cell lines in vitro or in vivo . These limitations have led to the development of more clinically relevant models, such as organoids or murine xenografts that utilize patient‐derived material; however, issues related to low take rate, long duration of establishment, and the associated costs constrain use of these models. This study demonstrates that ex vivo culture of freshly resected breast and prostate tumor specimens obtained from surgery, termed patient‐derived explants (PDEs), provides a high‐throughput and cost‐effective model that retains the native tissue architecture, microenvironment, cell viability, and key oncogenic drivers. The PDE model provides a unique approach for direct evaluation of drug responses on an individual patient's tumor, which is amenable to analysis using contemporary genomic technologies. The ability to rapidly evaluate drug efficacy in patient‐derived material has high potential to facilitate implementation of personalized medicine approaches. Abstract : This study describes an innovative preclinical model that has significant potential to accelerate translational cancer research outcomes. Breast and prostate tumors were cultured as patient‐derived explants (PDE), in a way that sustains the native tissue architecture, microenvironment, cell viability, and steroid receptor signaling. PDEs were responsive to hormones, therapeutic agents, and shRNA while in culture, allowing direct comparison of treatments within an individual's tumor using high‐throughput molecular approaches, including cistrome profiling.